Z dziejów szkolnictwa jezuickiego w Polsce. Wybór artykułów, Kraków 1994, ss. 258. - Żołądź, Dorota (Biuletyn Historii Wychowania, 1995)
Z dziejów szkolnictwa jezuickiego w Polsce. Wybór artykułów, Kraków 1994, ss. 258.